A Framework for Navigating Institutional Review Board (IRB) Oversight in the Complicated Zone of Research - Parker, Gretchen E (Cureus, 2016)
The treatment therapies and technologies currently emerging from the rapidly evolving health care industry must undergo full examination in a clinical setting if they are to be marketed to the public. All elements of clinical studies involving human subjects must undergo thorough IRB review before study activities can commence. Regulations regarding IRB oversight apply to all clinical studies—including retrospective examinations of private medical data and identifiable biological samples. It is not uncommon for researchers to be unsure whether, or on what level, IRB review and oversight are required for a particular project. Yet, if human subjects or their private medical data are utilized in a study, peer-reviewed journals will require relevant IRB approval information be provided as a requirement for publication. This article examines IRB processes and review types, offers insight into the IRB decision-making process, and emphasizes the importance of engaging an IRB consultant early in the clinical study design process.